The Modelling of Data Dependencies for Executable Business Processes - Vaknin, Michael; Filipowska, Agata (Studia Oeconomica Posnaniensia, 2017)
Th e correctness, effectiveness, and efficiency of the business processes supported by information systems are becoming vital to organizations. Poor data quality may be the cause of losses related to organizational processes. There are numerous methods to assess and improve the quality of data within information systems. However, these methods oft en do not address the original source of these problems. Th is article presents a conceptual solution for dealing with the data quality issue within information systems. It focuses on an analysis of business processes being a source of requirements for information systems design and development. This analysis benefits information quality requirements, in order to improve data quality within systems emerging from these requirements.